2015
DOI: 10.1589/jpts.27.3451
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gait before and after superficial trunk muscle exercise and deep trunk muscle exercise

Abstract: [Purpose] The purpose of this study was to examine the effects of superficial trunk muscle and deep trunk muscle exercise on gait. [Subjects] The subjects were 45 young adults who voluntarily consented to participate. The subjects were divided into a control group, a superficial muscle exercise group, and a deep muscle exercise group with 15 participants in each group. [Methods] Each group performed the exercises 5 times a week for 4 weeks. A Gait Analyzer was used to measure the subjects’ gait. A one-way ANOV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Electromyography (EMG) has shown that reaching exercises performed in a seated position activate the erector spinae and abdominal muscles 5 ) . Furthermore, stability during walking relies on the coordinated activation of the trunk muscles 6 ) , and there is a positive correlation between trunk muscle thickness and walking speed 7 , 8 ) . The transversus abdominis (TrA) is a lateral abdominal muscle that plays a vital role in trunk control 9 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Electromyography (EMG) has shown that reaching exercises performed in a seated position activate the erector spinae and abdominal muscles 5 ) . Furthermore, stability during walking relies on the coordinated activation of the trunk muscles 6 ) , and there is a positive correlation between trunk muscle thickness and walking speed 7 , 8 ) . The transversus abdominis (TrA) is a lateral abdominal muscle that plays a vital role in trunk control 9 ) .…”
Section: Introductionmentioning
confidence: 99%